Effect of Green Pharmacy-Based MTM Education on Quality of Life among Elderly Patients with Type 2 Diabetes Mellitus - Junvidya Heroweti; Ulfa Filliana; Deshinta Dinda Nurrahmawati; Farhani Nur Rahmadania; Ananda Fiqi Salamah; Muhammad Irfan Bashir (JPSCR: Journal of Pharmaceutical Science and Clinical Research, 2026)
Diabetes Mellitus Type 2 (T2DM) is a chronic metabolic disease that commonly affects elderly (≥60 years) populations and significantly impacts patients' quality of life due to long-term pharmacotherapy and disease complications. Medication Therapy Management (MTM) has been recognized as an effective pharmacist-led intervention to optimize medication use and improve clinical outcomes. However, its integration with environmental sustainability principles remains limited. This study aimed to evaluate the effect of Green Pharmacy-based MTM education on quality of life among elderly patients with type 2 diabetes mellitus. A quasi-experimental study with a pretest-posttest control group design was conducted among 84 elderly patients at primary healthcare centers in Semarang, Central Java, Indonesia, from September to October 2025. The application of rational medication principles, as emphasized in Green Pharmacy-based MTM education, plays a crucial role in minimizing adverse effects and optimizing therapeutic outcomes. Quality of life was assessed before and after the intervention using the Diabetes Quality of Life (DQoL) questionnaire, accompanied by clinical monitoring of random blood glucose levels. The results showed that the intervention significantly improved quality of life compared to control (p<0.05). These findings highlight the potential of sustainable, pharmacist-led educational interventions to enhance diabetes management and patient-centered outcomes.